2022
DOI: 10.1177/11769351221132634
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Molecular Analysis Reveals 2 Distinct Subtypes of Pure Seminoma of the Testis

Abstract: Objective: Testicular germ cell tumors (TGCT) are the most common solid malignancy in adolescent and young men, with a rising incidence over the past 20 years. Overall, TGCTs are second in terms of the average life years lost per person dying of cancer, and clinical therapeutics without adverse long-term side effects are lacking. Platinum-based regimens for TGCTs have heterogeneous outcomes even within the same histotype that frequently leads to under- and over-treatment. Understanding of molecular differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 133 publications
(168 reference statements)
1
13
0
Order By: Relevance
“…Very recently, Medvedev et al 15 identified from the TCGA GCT cohort two subtypes of seminomas, i. e. subtype 1 with a high level of pluripotency, while subtype 2 showed attributes of reprogramming into a non-seminoma. Correlating the samples grouped into subtype 2 by Medvedev et al 15 to the seminoma samples with detectable FOXA2 expression identified in this study (Supporting information, Figure S1) shows that five of the eight (62.5%) FOXA2 + seminomas were grouped to subtype 2 (2G-AAHA, 2G-AAHN, ZM-AA0F, ZM-AA06, XE-AA0L) by Medvedev (2 to subtype 1 (XE-A9SE, YU-A912); 1 was not grouped (2G-AAG9)). Thus, the FOXA2 + seminoma identified in this study and the seminoma of subtype 2 from the Medvedev study might represent a similar subtype prone to differentiate into YST.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Medvedev et al 15 identified from the TCGA GCT cohort two subtypes of seminomas, i. e. subtype 1 with a high level of pluripotency, while subtype 2 showed attributes of reprogramming into a non-seminoma. Correlating the samples grouped into subtype 2 by Medvedev et al 15 to the seminoma samples with detectable FOXA2 expression identified in this study (Supporting information, Figure S1) shows that five of the eight (62.5%) FOXA2 + seminomas were grouped to subtype 2 (2G-AAHA, 2G-AAHN, ZM-AA0F, ZM-AA06, XE-AA0L) by Medvedev (2 to subtype 1 (XE-A9SE, YU-A912); 1 was not grouped (2G-AAG9)). Thus, the FOXA2 + seminoma identified in this study and the seminoma of subtype 2 from the Medvedev study might represent a similar subtype prone to differentiate into YST.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Medvedev et al 15 . identified from the TCGA GCT cohort two subtypes of seminomas, i. e. subtype 1 with a high level of pluripotency, while subtype 2 showed attributes of reprogramming into a non‐seminoma.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, Tregs have been shown to be closely associated with tumor staging and prognosis, and removal of Tregs can evoke effective anti-tumor immunity by eliminating the immune response to syngeneic tumors. In addition, myeloid-derived suppressor cells (MDSCs) are also widely present in peripheral blood and tumor tissues of EGCT patients ( 30 ). These cells include immature macrophages, granulocytes, dendritic cells (DCs), and so on.…”
Section: Formation Of Immunosuppressive Microenvironmentmentioning
confidence: 99%
“…After undergoing chemotherapy, patients with TGCT exhibited a decrease of 3.6 dB in hearing for each additional 100 mg/m2 of cumulative cisplatin dose 8,9 . Relapse occurs in approximately 20% of seminoma cases, and the underlying reasons for this phenomenon remain unclear 10 , however there are several well-known seminoma risk factors such as rete testis, lymphovascular invasion, cryptorchidism, mutations in KRAS and KIT genes 11,12 . Patients experiencing a relapse will receive further treatment involving chemotherapy and radiation therapy, which intensify the side effects considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Patients experiencing a relapse will receive further treatment involving chemotherapy and radiation therapy, which intensify the side effects considerably. Recently we discovered two distinct subtypes of pure seminoma of the testis based on omics data 13,14 . Two identified seminoma subtypes revealed significant differences in the rates of loss of heterozygosity, the level of expression of lncRNA associated with cisplatin resistance, the activity of double stranded DNA breaks repair mechanisms and the pluripotency stage.…”
Section: Introductionmentioning
confidence: 99%